Managementof squamos cell carcinoma of tongue in young men: case report - Israyani, Israyani; Argadianti, Ayu F.; Hendarti, Hening Tuti; P, Adiastuti E. (Journal of Case Reports in Dental Medicine, 2019)
Background: Oral Squamous cell carcinoma is the most common malignant neoplasm of the oral cavity, usually affecting individuals over 50 years of age. It rarely occurs in patients who are less than 40 years old. Purpose: This case report aim is to focuses on establishment of diagnosis, differential diagnosis, predisposition, and treatment planning related to the case. Case: This report describes a case of oral squamous cell carcinoma, staged T1N1M0 (stage III), involving the lateral border and ventral surface of the tongue of a 32-year old male patient, with no smoking or drinking habits. Initial tumor presentation was of deep ulceration and intense pain. Case Management: Patient has examination with autofluorence LED light, presence of bacterial growth, and FNA for establised diagnosis. Patient was given chlorine dioxide mouthwash and education for further treatment one of them is tomoterapi. Conclusions: Clinical features of deep ulceration, pain and induration may be a suspicious feature of oral cavity cancer, therefore early diagnosis of oral squamous cell carcinoma determines prognosis.Keywords: malignant, autofluoresence, tomoterap